The association between quality of sleep and health-related quality of life in nurses - Bagheri H; Shahabi Z; Ebrahimi H; Alaeenejad F (Tehran University of Medical Sciences, 2006)
Background & Aim: Sleep is an important physiological process that has deep effects on psychological and physical health. This study carried out to investigate the association between quality of sleep and health-related quality of life in nurses. Methods & Materials: In this cross sectional and descriptive-analytic study, 127 nurses in Imam Hossein Hospital of Shahroud, Iran, during February and March 2006 were chosen enumeration and then their sleep quality and their quality of life in eight dimensions were measured with using Pittsburgh sleep quality index (PSQI) and 12-item short form health survey (SF-12) questionnaire and were compared. The data were analyzed using SPSS 11.5 software. Results: Upon to the results of this study, 25.2%, 70.9% and 3.9% of cases were working on morning shift, circulator shift and afternoon/night shifts respectively. Mean of time that they spend in bed were estimated 30.2 minute and 2.1% of subjects declare they get to sleep more than 30 minutes after going to bed. Mean of gotten up time in the morning in was at 6 and 58% of them described that they wakeup 1 hour earlier to anticipation time. According to the results, 35.5% of subjects have taken medicine (prescribed or "over the counter") to help them sleep. Spearman correlation coefficient test revealed a significant correlation (p<0.05) between the mean of Sleep Quality score and the mean of quality of life score in all dimensions in subjects. Conclusion: According to the results, quality of sleep is poor in majority of nurses and significantly has decreased their quality of life in different aspects, especially in general health, mental health and physical pain.